Value investing or investing in illiquidity? The profitability of contrarian investment strategies, revisited - Aron A. Gottesman; Gady Jacoby; Huijing Li (Financial Innovation, 2017)
Background: We investigate whether the success of contrarian investment strategies can be attributed to differences in the relative illiquidity of stocks categorized as value investments versus those categorized as glamour portfolios. Methods: Following Lakonishok et al. (J Financ 49:1541-1578, 1994), we assess the illiquidity characteristics of portfolios that underlie contrarian investment strategies that are based on the level of stock's book to market. Results: We find strong evidence that those portfolios characterized as value investments are associated with dramatically greater levels of illiquidity than glamour portfolios. We further demonstrate that strategies based on the illiquidity in the year prior to portfolio formation result in return characteristic of ostensibly contrarian strategies. Conclusions: These results suggest that the higher returns associated with contrarian investment strategies are the result of the higher illiquidity associated with value portfolios and represent compensation that the investor receives for accepting illiquidity. They also suggest that researchers should be cautious before attributing apparent anomalies to behavior-driven expectational errors rather than to other attributes unrelated to behavior, such as illiquidity.
Keywords: 650; Contrarian investment strategies; Illiquidity; Value portfolios; Growth portfolios; Book to market ratio